Extraction, isolation, structural characterization, and antioxidant activity of polysaccharides from elderberry fruit - Wei, Xinxin; Yao, Junxiu; Wang, Fangzhou; Wu, Dejun; Zhang, Rentang (Frontiers in Nutrition, 2022)
The isolation, purification, and antioxidant activity of polysaccharides extracted from elderberry fruits were studied. Two neutral polysaccharides (EFP-0, EFP-1) and three acidic polysaccharides (EFP-2, EFP-3, EFP-4) were isolated from elderberry. All five polysaccharides were composed of arabinose, galactose, glucose and other monosaccharides, with molecular weights of 1.7981×106, 7.0523×106, 7.7638×106, 4.3855×105 and 7.3173×105 Da respectively. Structural characterization showed that the backbone of EFP-2 consisted of →4)-Manp (1→4)-β-D-Glcp (1→ and →4)-β-D-Glcp (1→5)-α-L-Araf (1→units, and T-α-L-Araf (1→ and T-β-D-Galp (1→ residues were detected by methylation analysis and NMR analysis. In addition, MTT assay and zebrafish oxidative damage assay showed that EFP-2 had a protective effect on H2O2-damaged RAW264.7 cells in a dose-dependent manner, and zebrafish with the addition of EFP-2 would have low levels of ROS in vivo which showed significant antioxidant capacity. Therefore, the results showed that the elderberry polysaccharides have antioxidant activity and can be used as potential antioxidants in functional foods.